Огляд вимог до рецензування дипломних робіт - Даць, Ольга; Корж, Галина; Тимовчак-Максимець, Оксана (Видавництво Львівської політехніки, 2012)
This article presents the overview of the main requirements for writing diploma paper review, which characterizes the diploma project giving comments and suggestions. The paper gives the notion of diploma paper review, requirements to the reviewer and content of a review.
Keywords: рецензія; рецензування; рецензент; дипломна робота; Державна екзаменаційна комісія